Implanting Loop Recorders in a Hospital Unit versus the Electrophysiology Laboratory: A Retrospective Chart Review - Marie Paule Lafontant; Valerie E. Smith; Nohemi Sadule Rios; Marsha Camille Lambert (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2019)
Introduction: Cardiac arrhythmias and unexplained syncopal episodes remain a challenge for clinicians to diagnose. The recent creation of the smallest Implantable Loop Recorder (ILR) assists in identifying the causes behind cardiac and neurological events. The current study aimed to compare the practice of implanting loop recorders at the bedside in the Cardiac and Vascular Care Unit (CVCU) to implantations in the Electrophysiology Laboratory (EP Lab). Methods: This study was a retrospective review of electronic medical records. Data abstraction included implantation dates, time of admission and discharge, length of stay (LOS), number of healthcare staff involved, and cost of the procedure. Results: Over ten months, 63 ILRs were implanted in the EP Lab and 131 ILRs at the bedside. Patients LOS, on average, in the EP Lab was five hours versus four hours at the bedside. Five staff were required to implant the ILR in the EP Lab, and two at the bedside. Based on 63 cases in the EP Lab, the hospital generated revenue of $395,640, whereas the 131 cases at the bedside generated revenue of $822,680. This resulted in an increase in revenue of $427,040. Discussion: A higher number of procedures were done at the bedside leading to a decreased average length of stay, number of staff involved, cost of the procedure, and a reduction in waiting time for patient admission and discharge.